Propagation of Human Corneal Endothelial Cells: A Novel Dual Media Approach. Issue 2 (February 2015) - Peh, Gary S. L.; Chng, Zhenzhi; Ang, Heng-Pei; Cheng, Terence Y. D.; Adnan, Khadijah; Seah, Xin-Yi; George, Benjamin L.; Toh, Kah-Peng; Tan, Donald T.; Yam, Gary H. F.; Colman, Alan; Mehta, Jodhbir S.
Corneal endothelium-associated corneal blindness is the most common indication for corneal transplantation. Restorative corneal transplant surgery is the only option to reverse the blindness, but a global shortage of donor material remains an issue. There are immense clinical interests in the development of alternative treatment strategies to alleviate current reliance on donor materials. For such endeavors, ex vivo propagation of human corneal endothelial cells (hCECs) is required, but current methodology lacks consistency, with expanded hCECs losing cellular morphology to a mesenchymal-like transformation. In this study, we describe a novel dual media culture approach for the in vitro expansion of primary hCECs. Initial characterization included analysis of growth dynamics of hCECs grown in either proliferative (M4) or maintenance (M5) medium. Subsequent comparisons were performed on isolated hCECs cultured in M4 alone against cells expanded using the dual media approach. Further characterizations were performed using immunocytochemistry, quantitative real-time PCR, and gene expression microarray. At the third passage, results showed that hCECs propagated using the dual media approach were homogeneous in appearance, retained their unique polygonal cellular morphology, and expressed higher levels of corneal endothelium-associated markers in comparison to hCECs cultured in M4 alone, which were heterogeneous and fibroblastic in appearance. Finally, for hCECs cultured using the dual media approach, global gene expression and pathway analysis between confluent hCECs before and after 7-day exposure to M5 exhibited differential gene expression associated predominately with cell proliferation and wound healing. These findings showed that the propagation of primary hCECs using the novel dual media approach presented in this study is a consistent method to obtain bona fide hCECs. This, in turn, will elicit greater confidence in facilitating downstream development of alternative corneal endothelium replacement using tissue-engineered graft materials or cell injection therapy.